ANTIMICROBIAL ACTIVITY OF MENTOFIN AND ITS EFFECT ON ANTIBODY RESPONSE OF BROILERS TO NEWCASTLE DISEASE VIRUS VACCINE - S. R. Rehman; K. Muhammad; T. Yaqub; M. S. Khan; K. Hanif; R. Yasmeen (Journal of Animal and Plant Sciences, 2013)
Mentofin is a herbal product containing 10 % eucalyptus oil, 10% menthol, 33% liquid builders and 47% saponins. Its antimicrobial activity in vitro against Newcastle Disease (ND) virus and urease producing bacteria, and its effect on antibody response of broilers to Newcastle Disease (ND) virus vaccine were evaluated. Mentofin at 0.5 % concentration inactivated the lentogenic strain of ND virus within 15 minutes at interaction temperature of 37 0C and at 0.01%inactivated Proteus vulgarus in nutrient broth while 0.0001% concentration inactivated the same bacteria in urease broth. For evaluating its effect on antibody response of broilers to ND virus vaccine, one hundred day old broiler chicks were divided in to four groups (A, B, C and D) with 25 birds in each. Each bird of group A and B was vaccinated against ND and each bird of group A and C was treated with Mentofin while birds of group D served as negative control. Anti-ND- HI antibody titer of all birds was monitored on 14, 21, 28 and 35 days of age. Mentofin treated broilers showed higher consistent antibody titer as compared to untreated broilers. These birds when given challenge infection on 35 days of age showed same protection as that of untreated vaccinated birds. However, un-vaccinated and Mentofin treated broilers showed higher protection than those of non-treated unvaccinated. Mentofin did not show any effect on weight gain and feed conversion ratio of the treated broilers. Moreover, droppings from Mentofin treated birds showed no urease producing bacteria while 100 percent droppings of the Mentofin untreated birds showed urease producing bacteria
Keywords: Mentofin; anti-NDV HI antibody titer; FCR; Urease producing bacteria; Ammonia